Mulheres na política a sub-representação feminina no legislativo municipal de Tocantinópolis - Sousa, Letícia Barroso de (Universidade Federal do Tocantins, 2023)
This monograph analyzes, supported by studies in the field of Political Science, the political under-representation of women in the Municipal Legislature of the city of Tocantinópolis - TO throughout successive elections, under a time frame of the elections that took place between the years 2004 and 2020. For this, the qualitative methodology was used in a thematic content analysis of interviews and questionnaires applied to councilors and former councilors of the city. It was identified that the unequal domestic workload to which women are subjected and the lack of financial resources for campaign are some barriers to the entry of more women to the area of political representation of the city.